PEMISAHAN ANION MENGGUNAKAN FASA DIAM HILIC IMIDAZOL PADA HYDROPHILIC INTERACTION LIQUID CHROMATOGRAPHY DENGAN PENAMBAHAN GARAM AMMONIUM ASETAT - Mayaserli, Dyna Putri (Sainstek : Jurnal Sains dan Teknologi, 2015)
The need to detect anions and cations in a variety of environmental water samples more rapidly along with the increasing environmental problems and the time required analytical methods are precise, fast, simple and can provide an accurate assessment. Hydrophilic Interaction Liquid Chromatography (HILIC) is an extremely precise technique for separating polar compounds or compounds that are hydrophilic. The purpose of this study is to assess the separation of anions using HILIC stationary phases imidazole in hydrophilic interaction liquid chromatography with the addition of ammonium acetate salt. From the research that has been done can be concluded Imidazoles HILIC can separate SCN- anion, NO 3, NO 2, Br, and I- BrO3- using acetonitrile mobile phase. The addition of salt Ammonium Acetate in the mobile phase can increase the sensitivity and selectivity of anions. So that the resulting peak sharper and bigger.Key words: HILIC Imidazol, anion, HILIC